Ecological and conceptual consequences of Arctic pollution. (25th September 2020) - Kirdyanov, Alexander V.; Krusic, Paul J.; Shishov, Vladimir V.; Vaganov, Eugene A.; Fertikov, Alexey I.; Myglan, Vladimir S.; Barinov, Valentin V.; Browse, Jo; Esper, Jan; Ilyin, Viktor A.; Knorre, Anastasia A.; Korets, Mikhail A.; et al.
Abstract: Although the effect of pollution on forest health and decline received much attention in the 1980s, it has not been considered to explain the 'Divergence Problem' in dendroclimatology; a decoupling of tree growth from rising air temperatures since the 1970s. Here we use physical and biogeochemical measurements of hundreds of living and dead conifers to reconstruct the impact of heavy industrialisation around Norilsk in northern Siberia. Moreover, we develop a forward model with surface irradiance forcing to quantify long‐distance effects of anthropogenic emissions on the functioning and productivity of Siberia's taiga. Downwind from the world's most polluted Arctic region, tree mortality rates of up to 100% have destroyed 24, 000 km 2 boreal forest since the 1960s, coincident with dramatic increases in atmospheric sulphur, copper, and nickel concentrations. In addition to regional ecosystem devastation, we demonstrate how 'Arctic Dimming' can explain the circumpolar 'Divergence Problem', and discuss implications on the terrestrial carbon cycle. Abstract : In this study, we present the combined evidence from dendroecology, biogeochemistry and process‐based forward modelling to address the direct and indirect effects of industrial pollution on the functioning and productivity of boreal forest ecosystems. In addition to the quantification of the exceptional rate of environmental devastation around Norilsk, the world's most polluted Arctic region, we demonstrate that anthropogenic‐induced 'Arctic Dimming' can explain the yet unresolved 'Divergence Problem' in tree‐ring research.